LAYANAN INFORMASI AKADEMIK STMIK MARDIRA INDONESIA VIA SMS BERBASIS OPEN SOURCE - Dadi Rosadi; Kuat Santoso (STMIK Mardira Indonesia, Bandung, 2015)
Academic information service in and education institute is a real important. Various problems grows be with the rise of technology until grows various ideas and creativity to realize process akademik fluently effective. With presents it technology SMS (Short Message Service) each and everyone can receive information quickly, brief and precise. Technological solidarity can rise a solution alternative of that all requirement oh student as client of management can be fufilled. Application service giving academic information via this SMS many developed in so many technique. Starts from structured programming technique so is developed applies object-oriented programming technique (OOP). The application of this developed applies object-oriented programming technique (OOP) with the builder application applies programming with java and the Netbeans application as the application of IDE java. Excellence from application developed is apply application to base on open Source either from the application of developer and also the supporter application which in expenditure of expense of from payee side can be told zero rupiahs. From the application of developer of using Linux Ubuntu 9.10 karmic as operating system bases on openSource. And the application of Gammu as machine from sms gateway which also is the application of openSource. For the future of development, the application of this can be developed again by refers to insuffiency side from fitur the application of this like system collaboration with bank agent through sms banking. Keywords: Academic, SMS, Java, Open Source Abstract Layanan informasi akademik dan lembaga pendidikan adalah nyata penting. Berbagai masalah tumbuh bersama munculnya teknologi sampai berkembang berbagai ide dan kreativitas untuk mewujudkan proses akademik lancar efektif. Dengan SMS hadirnya teknologi (Short Message Service) setiap orang dapat menerima informasi dengan cepat , singkat dan tepat. Teknologi dapat meningkat alternatif solusi dari semua kebutuhan oleh mahasiswa sebagai klien dari manajemen sehingga dapat terpenuhi. Layanan aplikasi informasi akademik via SMS ini banyak dikembangkan dalam berbagai teknik. Mulai dari teknik pemrograman terstruktur sehingga menggunakan teknik pemrograman berorientasi objek (OOP). Aplikasi ini dikembangkan menggunakan teknik pemrograman berorientasi objek (OOP) dengan aplikasi pembangun berlaku pemrograman dengan java dan aplikasi Netbeans sebagai aplikasi java IDE. Keunggulan dari aplikasi yang dikembangkan adalah menerapkan aplikasi untuk berbasis sumber terbuka baik dari aplikasi pengembang dan juga aplikasi pendukung yang dalam pengeluaran biaya dari sisi penerima pembayaran bisa dikatakan nol rupiah. Dari aplikasi pengembang menggunakan Ubuntu Linux 9.10 karma sebagai basis sistem operasi pada open source. Dan penerapan Gammu sebagai mesin dari sms gateway yang juga merupakan aplikasi open source. Untuk masa depan pembangunan, penerapan ini bisa dikembangkan lagi dengan mengacu pada sisi kekurangan dari fitur penerapan sistem ini bekerja sama seperti dengan agen perbankan melalui sms banking. Kata Kunci: Academik, SMS, Java, Open Source